The Concept and Expression in the Courts of the Revision of Judicial Acts that Have Entered into Force Due to Newly Discovered Circumstances (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes a specific important aspect of the consideration of cases by administrative courts operating in the Republic of Uzbekistan. The Institute for revising the decision decisions made by the administrative courts on cases that were reopened after they entered into legal force was analyzed. The article compare opinions and concepts of legal scholars working in the law sphere and analyzes norms given in the legislative acts, namely The code of Administrative court proceedings, The code of Civil Procedure and the code of Economy Procedure.